DEVELOPMENT OF HERB BASED PHARMACEUTICAL INDUSTRY IN UTTARAKHAND STATE (International Journal of Ayurveda and Pharma Research, 2015)
Uttarakhand has been known as a place for best medicinal plants since ancient times as referred in original Ayurvedic classics i.e. Charaka Samhita (1000 BC). In recent years the pharmaceutical industries have realized its potential medicinal flora because of diversified agro climatic zone as well as less environmental pollution as 63% of the land belongs to forest. Thus the state has immense potential area to cater the demand to produce best Ayurvedic products nutraceuticals, cosmoceuticals and Agro-chemical based industrial products. Herb based Pharmaceutical industry is having great potential and opportunities for development in future because of acetate demand of the medicinal plants & their value added products are well accepted in Domestic & International Market as Ayurvedic, Unani and Siddha, Homoeopathic medicines, Herbal Nutraceuticals, Herbal Cosmoceutical, Herbal Health drinks, Dietary Health Supplements, Medicinal Plants / Crude Drugs, Herbal Extracts / Concentrates, Veterinary Medicines, Health Foods. Various issues & challenges of Herbal Pharmaceutical Industries in Uttarakhand need proper attention of policy makers in favour of small industries. If, the challenges & issues related to development of Herbal sector in Uttarakhand is addressed the State could be the capital of Herbs in India.